Clinical utility of EMSE and STESS in predicting hospital mortality for status epilepticus. (August 2018) - Zhang, Yu; Chen, Deng; Xu, Da; Tan, Ge; Liu, Ling
Highlights: The hospitalization mortality rate of status epilepticus was evaluated using the EMSE and STESS scales. A study of the western China population and the use of the latest status epilepticus. The mortality rates of patients with different types of status epilepticus were assessed separately. It is the first time to study the hospital mortality for NCSE. Both STESS and EMSE were less useful predicting in-hospital mortality in NCSE compared to CSE. Abstract: Purpose: To explore the applicability of the epidemiology-based mortality score in status epilepticus (EMSE) and the status epilepticus severity score (STESS) in predicting hospital mortality in patients with status epilepticus (SE) in western China. Furthermore, we sought to compare the abilities of the two scales to predict mortality from convulsive status epilepticus (CSE) and non-convulsive status epilepticus (NCSE). Method: Patients with epilepsy (n = 253) were recruited from the West China Hospital of Sichuan University from January 2012 to January 2016. The EMSE and STESS for all patients were calculated immediately after admission. The main outcome was in-hospital death. The predicted values were analysed using SPSS 22.0 receiver operating characteristic (ROC) curves. Result: Of the 253 patients with SE who were included in the study, 39 (15.4%) died in the hospital. Using STESS ≥4 points to predict SE mortality, the area under the ROC curve (AUC) was 0.724 (P < 0.05). Using EMSE ≥79 points, the AUC was 0.776 (P < 0.05). To predict mortality in NCSE, STESS ≥2 points was used and resulted in an AUC of 0.632 (P > 0.05), while EMSE ≥90 points gave an AUC of 0.666 (P > 0.05). Conclusions: The hospital mortality rate from SE in this study was 15.4%. Those with STESS ≥4 points or EMSE ≥79 points had higher rates of SE mortality. Both STESS and EMSE are less useful predicting in-hospital mortality in NCSE compared to CSE. Furthermore, the EMSE has some advantages over the STESS.